Meteorological Influences on Anthropogenic PM2.5 in Future Climates: Species Level Analysis in the Community Earth System Model v2. Issue 2 (2nd February 2022) - Banks, Alison; Kooperman, Gabriel J.; Xu, Yangyang
Abstract: Biomass and fossil fuel burning impact air quality by injecting fine particulate matter (PM2.5 ) and its precursors into the atmosphere, which poses serious threats to human health. However, the surface concentration of PM2.5 depends not only on the magnitude of emissions, but also secondary production, transport, and removal. For example, in response to greenhouse gas driven warming, meteorological conditions that govern aerosol removal, primarily through rainfall and wet deposition, could shift in pattern, frequency, and intensity. This climate change driven process can impact air quality even without changes in aerosol emissions. In this experiment, we conduct new simulations by fixing aerosol emissions at present‐day levels in the Community Earth System Model Version 2, but increasing greenhouse gases through the 21st century. In our results, the changes in patterns and intensity of PM2.5 are found to be associated with precipitation (via aerosol removal), temperature (via secondary organic aerosol (SOA) formation), and moisture and clouds (via sulfate production). A decrease in wet day frequency (∼1.2% global mean) contributes to increases in the surface concentrations of black carbon, primary organic matter, and sulfate in many regions. This is offset in some regions by an upward vertical shift in the level where SOA forms, which contributes to higher column burden but lower surface concentration. These results highlight a need, using a variety of modeling tools, to continually reassess aerosol emissions regulations in response to anticipated climate changes. Key Points: In 21st century simulations with fixed present‐day aerosol emissions, air quality worsens in many parts of South America, Africa and Asia Surface concentrations of sulfate, black carbon and primary organic matter increase globally, while secondary organic matter declines Greenhouse gas driven changes in rainfall frequency, temperature, and moisture availability impact the production and removal of aerosols